2016
DOI: 10.1109/tifs.2016.2526963
|View full text |Cite
|
Sign up to set email alerts
|

A Game-Theoretic Framework for Optimum Decision Fusion in the Presence of Byzantines

Abstract: Abstract-Optimum decision fusion in the presence of malicious nodes -often referred to as Byzantines -is hindered by the necessity of exactly knowing the statistical behavior of Byzantines. By focusing on a simple, yet widely studied, set-up in which a Fusion Center (FC) is asked to make a binary decision about a sequence of system states by relying on the possibly corrupted decisions provided by local nodes, we propose a game-theoretic framework which permits to exploit the superior performance provided by op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Finally, we should note that we do not assume any pattern of the bias y a i (k) for i ∈ I, i.e., the malicious bias injected may be correlated across the compromised sensors and correlated over time. Compared to the independence assumption in [5]- [10], [13], our assumption improves the effectiveness of the attacker and is more realistic in the sense that the attacker is malicious and will do whatever it wants. Remark 1.…”
Section: A Attack Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we should note that we do not assume any pattern of the bias y a i (k) for i ∈ I, i.e., the malicious bias injected may be correlated across the compromised sensors and correlated over time. Compared to the independence assumption in [5]- [10], [13], our assumption improves the effectiveness of the attacker and is more realistic in the sense that the attacker is malicious and will do whatever it wants. Remark 1.…”
Section: A Attack Modelmentioning
confidence: 99%
“…The authors in [11] showed that the optimal detector is of a threshold structure when the fraction of Byzantine sensors is less than 0.5. A zero-sum game was formulated in each of [12]- [14], among which a closed-form equilibrium point of attack strategy and detector was obtained in [14], computation efficient and nearly optimal equilibrium point (exact equilibrium point only in certain cases) was obtained in [12], and numerical simulations were used to study the equilibrium point in [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the attacker will gain nothing from the selfish PUE attack. Also, the defender cannot distinguish the PU signal from the attacker's signal 7 . We hence obtain the payoff of each player for a pair of actions regarding the presence of the PU at the t th channel as given in Table I.…”
Section: A Game Elementsmentioning
confidence: 99%